On-surface synthesis of organocopper metallacycles through activation of inner diacetylene moieties. Issue 38 (7th September 2021) - Cirera, Borja; Riss, Alexander; Mutombo, Pingo; Urgel, José I.; Santos, José; Di Giovannantonio, Marco; Widmer, Roland; Stolz, Samuel; Sun, Qiang; Bommert, Max; Fasel, Roman; Jelínek, Pavel; et al.
Abstract : The diacetylene skeletons of DNBD precursors are attacked on Cu(111) by copper adatoms resulting in the synthesis of organocopper metallacycles. Abstract : The design of organometallic complexes is at the heart of modern organic chemistry and catalysis. Recently, on-surface synthesis has emerged as a disruptive paradigm to design previously precluded compounds and nanomaterials. Despite these advances, the field of organometallic chemistry on surfaces is still at its infancy. Here, we introduce a protocol to activate the inner diacetylene moieties of a molecular precursor by copper surface adatoms affording the formation of unprecedented organocopper metallacycles on Cu(111). The chemical structure of the resulting complexes is characterized by scanning probe microscopy and X-ray photoelectron spectroscopy, being complemented by density functional theory calculations and scanning probe microscopy simulations. Our results pave avenues to the engineering of organometallic compounds and steer the development of polyyne chemistry on surfaces.